Kematangan Karier: Peran Future Time Perspective dan Kecerdasan Emosional - Qania Alivia Anindita; Utik Bidayati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to examine the roles of future time perspective and emotional intelligence in influencing the career maturity of students from universities in Yogyakarta. The study used 100 samples collected through questionnaires. The data were processed using confirmatory factor analysis with SPSS version 25 software. The analysis results show that future time perspective and emotional intelligence have a positive effect on students' career maturity, both partially and simultaneously. These findings indicate that students who have a clear outlook on the future and good emotional management skills tend to be better prepared to plan and make decisions regarding their careers. This research contributes theoretically by reinforcing the conceptual model connecting individual psychological factors with career readiness. Practically, this result can serve as a follow-up plan for the university to enhance the effectiveness of career guidance and counseling programs, focusing on the development of students' future time perspective and emotional intelligence.